The Oxford handbook of strategic sales and sales management - Cravens, David W.; Le Meunier-FitzHugh, Kenneth; Piercy, Nigel (Oxford : Oxford University Press, 2011)
'The Oxford Handbook of Strategic Sales and Sales Management' is a comprehensive overview of the latest research in the area by leading international academics. The handbook is suitable for academics, professionals, and those taking professional qualifications in sales and marketing.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Marketing -- Management; Sales management